A Case of Mild Encephalopathy with a Reversible Splenial Lesion Associated with G5P[6]Rotavirus Infection. (13th November 2013) - Matsuoka, Tsuyoshi; Yodoshi, Toshifumi; Sugai, Misaki; Hiyane, Masato; Matsuoka, Takashi; Akeda, Hideki; Ohfu, Masaharu; Komoto, Satoshi; Taniguchi, Koki
Abstract : We report a case of mild encephalopathy with a reversible splenial lesion (MERS) associated with acute gastroenteritis caused by rotavirus (RV) infection. The patient (male, 4 years and 3 months old) was admitted to our hospital for diarrhea and afebrile seizures. Head MRI revealed a hyperintense signal in the splenium of the corpus callosum on DWI and a hypointense signal on the ADC-map. After awakening from sedation, the patient's disturbance of consciousness improved. On day 5 after admission of the illness, the patient was discharged from the hospital in a good condition. Electroencephalography on day 2 after admission was normal. On day 8 of admission, head MRI revealed that the splenial lesion had disappeared. RV antigen-positive stools suggested that RV had caused MERS. This RV genotype was considered to be G5P[6]; it may have spread to humans as a strain reassortment through substitution of porcine RV into human RV gene segments. This extremely rare genotype was detected first in Japan and is not covered by existing vaccines; this is the first sample isolated from encephalopathy patients. Few reports have investigated RV genotypes in encephalopathy; we believe that this case is valuable for studying the relationship between genotypes and clinical symptoms.